To Evaluate Combined Efficacy of Amrutadya Guggulu and Udvartana followed by Bashpa Sweda in the Management of Sthaulya (International Journal of Ayurveda and Pharma Research, 2024)
Obesity (Sthaulya) is increasing at an alarming rate in developed industrialized countries which are undergoing rapid nutrition and lifestyle disorders like Diabetes mellitus (T2DM), Coronary Heart Disease (CHD), hypertension. In Ayurveda, Sthaulya (obesity) is regarded as Medoroga, a disorder of Meda Dhatu which includes fat tissue and fat metabolism. In Ayurveda Sthaulya is regarded as Medoroga. In Sthaulya Meda causes obstruction all Strotasa which leads to of Koshthasthit Saman Vayu Vriddhi, which in turn causes Jatharagnivardhana. It leads to Medadhatvagni Mandya and augmentation of Meda which results in Chalaspika, Chalaudara, Chala stana. According to WHO World Health Statistics Report 2012, globally one in 6 adults are obese and nearly 2.8 million individuals die each year due to overweight. Amrutadya Guggulu shows Rasa-Katu, Tikta, Kashaya, Guna-Laghu, Ruksha and Virya-Ushna, Vipaka-Katu, Dosha, Karma-Kapha Vatashamaka is effective in the management of Sthaulya. The ingredients of Udvartana Triphala (Kaphahara, Deepan), Musta, Darvi, Devdaru are Tikta, Kashay, Laghu, Ruksha Gunatamak having Sthaulyahara property. Bashpa Sweda given after Udvartana will make Vilayana of Vikruta meda. Due to this property, it breaks the Samprapti of Sthaulya. Hence the present attempt is done to encompass the upto date comprehensive literature to study the mode of action of Amrutadya Guggulu and Udvartna followed by Bashpa Sweda in the management of Sthaulya w.s.r. to Ayurvedic properties. Total 40 patients were enrolled in this study, significant result was seen in all subjective criteria, also 4 to 4.5kg weight loss is seen in all patients. For statistical analysis paired student ‘t’ test, Wilcoxon test were used.